Livelihood of FKIP Alumni in Developing Businesses: A Case Study in Mendalo Indah, Jambi Luar Kota District, Muaro Jambi Regency - Gustina; Mayasari; Muazza; Ahmad Rifki (Indonesian Scientific Publication, 2026)
Livelihood is an individual's effort to maintain and improve the sustainability of life, one of which is through entrepreneurial activities. This study aims to describe and understand the experiences of FKIP alumni in developing and maintaining businesses in Mendalo Indah, Muaro Jambi Regency, using a phenomenological case study approach with two informants. Data were collected through in-depth interviews, field observations, and documentation, then analyzed using NVivo to identify themes related to livelihood assets, namely human resources (education, skills, experience) and financial capital (initial capital, income). The results show that human resources play a major role as assets in business development and sustainability, particularly through the alumni's ability to interpret experiences, manage knowledge and skills, and adapt to business challenges. Financial capital functions as a supporting factor, but is relatively secondary. These findings confirm that the success of FKIP alumni businesses is determined more by the ability of individuals to manage and interpret livelihood assets adaptively in the local social and economic context, rather than by the amount of financial capital alone.